Ethical leadership in the Use of Artificial Intelligence in Organizations - Sevila Nurul Khusaini; Nabila Dzata Dini; Ach. Zaki Mubarok; Mochammad Isa Anshori (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The rapid development of Artificial Intelligence (AI) has brought about significant changes in modern organizational practices, particularly in data-driven decision-making and the enhancement of operational efficiency. Nevertheless, this development has also generated various ethical issues, such as algorithmic bias, limited transparency, and concerns regarding accountability. This study aims to conceptually examine the role of ethical leadership in directing the responsible use of AI within organizations. The study employs an integrative literature review approach through the review of relevant scholarly literature, involving systematic search procedures, selection based on inclusion and exclusion criteria, and analysis using content analysis, thematic analysis, and conceptual synthesis. The findings reveal that ethical leadership functions as an important normative mechanism in ensuring that AI implementation remains aligned with the principles of fairness, transparency, and social responsibility. In addition, the findings indicate that the success of AI governance is not determined solely by technical dimensions, but depends heavily on leadership capacity to manage ethical risks and build stakeholders’ trust. This study offers a conceptual contribution by integrating ethical leadership and AI governance into a coherent analytical framework, while also providing practical implications for organizations in designing AI strategies that are both sustainable and ethically responsible.